2017
DOI: 10.1038/s41598-017-14423-8
|View full text |Cite
|
Sign up to set email alerts
|

Norrin protects optic nerve axons from degeneration in a mouse model of glaucoma

Abstract: Norrin is a secreted signaling molecule activating the Wnt/β-catenin pathway. Since Norrin protects retinal neurons from experimental acute injury, we were interested to learn if Norrin attenuates chronic damage of retinal ganglion cells (RGC) and their axons in a mouse model of glaucoma. Transgenic mice overexpressing Norrin in the retina (Pax6-Norrin) were generated and crossed with DBA/2J mice with hereditary glaucoma and optic nerve axonal degeneration. One-year old DBA/2J/Pax6-Norrin animals had significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…ERGs were recorded according to a procedure described previously [38,39]. Additionally, responses to flickering stimuli (intensity 0.5 log cds/m2) with frequencies ranging from 4 to 25 Hz were recorded.…”
Section: Electroretinogram Recordingmentioning
confidence: 99%
“…ERGs were recorded according to a procedure described previously [38,39]. Additionally, responses to flickering stimuli (intensity 0.5 log cds/m2) with frequencies ranging from 4 to 25 Hz were recorded.…”
Section: Electroretinogram Recordingmentioning
confidence: 99%
“…Nevertheless, DBA/2J mice made significant contribution to advances in glaucoma research and served as a valuable tool for translational research in glaucoma 24 37. Recently, a study reported ameliorated optic nerve degeneration in transgenic mice overexpressing Norrin crossed with DBA/2J mice (DBA/2J/Pax6-Norrin mice), providing a possible therapeutic target for glaucoma 38. Norrin is a secreted signalling molecule activating the Wnt/β-catenin pathway and protects retinal neurons after NMDA injection,39 suggesting that an activator of Norrin and its downstream signalling might be useful to prevent glaucomatous damage in human patients.…”
Section: Animal Models Of Glaucomamentioning
confidence: 99%
“…In our current study, we found an enhanced expression of Lif after treatment of wild-type mice retinae with NMDA and Norrin. However, in a mouse model with a chronic degeneration of RGC and an additional overexpression of Norrin in the retina, we also observed a protective effect of Norrin but no induction of Lif [45]. It is most likely, that other factors could be required for the Norrin-mediated induction of Lif after acute excitotoxic retinal damage.…”
Section: Discussionmentioning
confidence: 56%